Utilization of coal bottom ash as lightweight aggregate in concrete production: A review - Al Biajawi, Mohammad I.; Rahimah, Embong; Adli Hilmi, Azmi; Norasyikin, Ismail (Springer Singapore, 2024)
Concrete is one of the building materials most in demand worldwide. Nevertheless, the increasing demand for concrete in the global construction sector requires an increase in the extraction of natural resources such as stone, sand, and various similar materials, resulting in the degradation of the natural environment. Consequently, the demand for construction aggregates has increased tremendously in the last decade. Currently, they are sourced from the main stone and sand deposits. Aggregates, one of the components of concrete, if indiscriminately extracted from primary resources, would cause an environmental problem. In particular, the large quantities of residual materials generated by coal combustion have underscored the need to develop viable reuse options for these high-volume pollutants. Coal Bottom Ash (CBA) is a type of industrial waste generated from coal combustion in thermal power plants. Due to their harmful impacts on the natural world and the health of the general population, the huge amounts of CBA waste generated annually by thermal power plants and improper disposal in landfills have caused major environmental problems. This review study aims to highlight the findings to date on using CBA as a lightweight aggregate in concrete production. Specifically, the effects of CBA as a lightweight aggregate on fresh and mechanical properties of concrete are discussed. Overall, concrete’s fresh and mechanical properties can be improved by using CBA as a lightweight aggregate in appropriate amounts. However, further studies are needed to assess the possibility of employing CBA as a lightweight aggregate in large quantities to produce high-performance concrete that is also durable.